P8 Tests of recent HIV infection in clinical practice: the patient perspective. (23rd May 2012) - Anderson, E R; Taegtmeyer, M; Delpech, V; Chawla, A; Gilbart, V
Abstract : Background: A test for recent infection (avidity test) is offered for all patients newly diagnosed with HIV in England and Wales as part of an HIV incidence surveillance programme. The UK is currently the only country to return these results to individual patients. Objectives: To determine the acceptability and patient experience of receiving a RITA test result soon after HIV diagnosis. Methods: This was a qualitative study using semi-structured interviews. 14 people recently diagnosed with HIV who had a RITA result consented to participate. Analyses were based on the framework method using N-Vivo software. Interviews were transcribed, coded and emergent themes identified. Results: All participants agreed that the more information available to them about the possible duration of infection the better. Unsurprisingly the HIV diagnosis and the emotions and practical issues associated with it had far more impact than the RITA result. None of the participants experienced any problems with former partners as a consequence of their RITA result although some could see the theoretical potential for such problems. "Recently infected" RITA results were felt to be potentially useful for identifying "at risk" partners. However partner notification was not altered in the study group because the individuals concerned had other reasons to suspect recent infection. Other major themes identified were the perceived stigma; the difficulty of sharing the diagnosis of HIV with family and friends; and the many conflicting emotions that people had to deal with at diagnosis including anger, grief, self-blame, fear and depression. Conclusion: RITA testing is a potentially useful epidemiological tool. These interviews demonstrated that receiving a RITA result, while useful to some people, is a minor issue compared with dealing with the HIV result itself. Reassuringly none of the participants reported negative outcomes from receiving the RITA result.